2010
DOI: 10.1007/s12289-010-0770-8
|View full text |Cite
|
Sign up to set email alerts
|

FEM numerical simulation of the warm and hot upsetting sliding test

Abstract: For bulk forming applications involving friction, the classical Coulomb-Amonton and Tresca-constant friction laws are not representative of the actual phenomenon when large changes in the contact pressure conditions occur. In order to address these issues, alternative friction laws has been proposed in the last decade. The present paper deals with the analysis of the stress distributions during the Warm and Hot Upsetting Sliding Test for further identification of friction parameters. A first part of the paper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…However, the compression ratio of this test is only about 50 percent and a friction test that allows a larger surface area expansion ratio is needed. In addition, reports of friction tests simulating hot extrusion and hot forging include the two-cylinder crossed friction test by Kalin et al [5][6][7] and the Warm and Hot Upsetting Sliding Test (WHUST) by Dubar et al [8][9][10] as examples of hot friction tests. Although these have been reported, there are few examples of friction tests simulating hot extrusion and hot forging.…”
Section: Introductionmentioning
confidence: 99%
“…However, the compression ratio of this test is only about 50 percent and a friction test that allows a larger surface area expansion ratio is needed. In addition, reports of friction tests simulating hot extrusion and hot forging include the two-cylinder crossed friction test by Kalin et al [5][6][7] and the Warm and Hot Upsetting Sliding Test (WHUST) by Dubar et al [8][9][10] as examples of hot friction tests. Although these have been reported, there are few examples of friction tests simulating hot extrusion and hot forging.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the difficulty of characterising the contact in a real process, many studies have approached the problem using laboratory tests. For this purpose, test methods such as upsetting-sliding [4,5], T-shape compression [6], Pin-on-disc [7] or the widespread ring compression [8,9] have been used. However, Joun et al [8] concluded that the friction evaluation curves achieved by means of the ring compression test were irrelevant for the hot rolling process that they analysed.…”
Section: Introductionmentioning
confidence: 99%